2019
DOI: 10.3389/fpsyt.2019.00261
|View full text |Cite|
|
Sign up to set email alerts
|

Early Trauma and Cognitive Functions of Patients With Schizophrenia

Abstract: Aim: The following work aims to investigate the putative correlation between early trauma and cognitive functions, as well as psychotic symptoms and cognitive functions, in individuals diagnosed with schizophrenia. Methods: A quantitative assessment was performed with 20 individuals diagnosed with schizophrenia according to the 5th edition of the Diagnostic and Statistical Manual (DSM-5) criteria and who were in ongoing outpatient treatment in Psychosocial Care Centres in Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…SCZ is a multifactorial brain disorder that can manifest as a range of symptoms, including cognitive, behavioral, and emotional deficits with delusions, hallucinations, or disorganized thinking (Tandon et al ; Lally et al ; Carrilho et al ). Similar to MDD, research data back to the early 1970s established differences in CSF DβH activity in SCZ patients (Dunner et al ; Wise and Stein ).…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
“…SCZ is a multifactorial brain disorder that can manifest as a range of symptoms, including cognitive, behavioral, and emotional deficits with delusions, hallucinations, or disorganized thinking (Tandon et al ; Lally et al ; Carrilho et al ). Similar to MDD, research data back to the early 1970s established differences in CSF DβH activity in SCZ patients (Dunner et al ; Wise and Stein ).…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
“…Child abuse has been linked to physical, social, cognitive and psychological problems in adulthood (McNeal and Amato, 1998;Adams, 2006;Adhia et al, 2019). Substantial evidence has shown that violence against children is positively associated with their suffering from posttraumatic stress disorder, depression, anxiety and low levels of selfesteem and self-efficacy (Carrilho et al, 2019;Haj-Yahia et al, 2019).…”
Section: Consequences Of Child Maltreatmentmentioning
confidence: 99%
“…Cognitive impairment is highly prevalent in schizophrenia, possibly because both psychotic symptoms and impaired cognition share similar etiology – genetic and/or environmental features [ 31 ]. Accordingly, physical or emotional trauma during childhood may cause cognitive impairment and increase the risk of developing schizophrenia or other mental disorders later in life [ 32 ]. Childhood maltreatment and neglect are known to have a detrimental impact on the cognitive functioning of patients with schizophrenia and bipolar disorder [ 33 ].…”
Section: Introductionmentioning
confidence: 99%